1992
DOI: 10.1111/j.1365-2621.1992.tb08092.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Comparison of the Stability of Anthocyanins from Brassica oleracea and Tradescantia pallida in Non‐Sugar Drink Model and Protein Model Systems

Abstract: The Trudescantiu pallida anthocyanins were about 29 times more stable in a nonsugar drink model system than red cabbage (Brussica oleracea) anthocyanins, and 15 times in a fish protein system. The degradation of the anthocyanins from both sources in a nonsugar drink model was logarithmic rather than linear. The mechanism for logarithmic relationship was assumed to be the difficulty of water molecules diffusion to the hydrophobic center formed by the acyl groups and the aglycone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 14 publications
(5 reference statements)
2
9
0
Order By: Relevance
“…. dation may follow linear (Baublis et al, 1994) or nonlinear degradation rates, probably due to folding of acyl molecules protecting the aglycon (Shi et al, 1992d;Baublis et al, 1994). Regression analysis showed that anthocyanin degradation during storage at 25ЊC fitted a quadratic model for our treatments.…”
Section: Chemistry/biochemistrymentioning
confidence: 82%
“…. dation may follow linear (Baublis et al, 1994) or nonlinear degradation rates, probably due to folding of acyl molecules protecting the aglycon (Shi et al, 1992d;Baublis et al, 1994). Regression analysis showed that anthocyanin degradation during storage at 25ЊC fitted a quadratic model for our treatments.…”
Section: Chemistry/biochemistrymentioning
confidence: 82%
“…However, there is a continuing effort to produce anthocyanin-based colorants which have improved stability. Acylated anthocyanin pigments show greater stability during processing and storage (Bassa and Francis, 1987;Hong and Wrolstad, 1990;Murai and Wilkins, 1990;Rommel et al, 1992;Shi et al, 1992). These acylated pigments also respond differently to pH change than do non-acylated ones (Price and Wrolstad, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity to bleaching by sulphur dioxide (18) and chemical conversions at pH values of above pH 4.0 (19) are limiting factors in the use of anthocyanins as food colorants. Reports of anthocyanins which are stable in food systems over a wide pH range revived the interest in their use as natural colorants (18,(20)(21)(22). Among other modifications, acylation of the anthocyanin molecule was found to be one factor leading to an increased color stability (23).…”
Section: Anthocyaninsmentioning
confidence: 98%